Tiered Reinforcement Learning: Pessimism in the Face of Uncertainty and Constant Regret - Huang, Jiawei; Zhao, Li; Qin, Tao; Chen, Wei; Jiang, Nan; Liu, Tie-Yan (Proceedings of the 36th Conference on Neural Information Processing Systems (NeurIPS), 2022)
We propose a new learning framework that captures the tiered structure of many real-world user-interaction applications, where the users can be divided into two groups based on their different tolerance on exploration risks and should be treated separately. In this setting, we simultaneously maintain two policies π^[[O]] and π^[[E]]: π^[[O]] (O'' for online'') interacts with more risk-tolerant users from the first tier and minimizes regret by balancing exploration and exploitation as usual, while π^[[E]] (E'' for exploit'') exclusively focuses on exploitation for risk-averse users from the second tier utilizing the data collected so far. An important question is whether such a separation yields advantages over the standard online setting (i.e., π^[[E]]=π^[[O]]) for the risk-averse users. We individually consider the gap-independent vs. gap-dependent settings. For the former, we prove that the separation is indeed not beneficial from a minimax perspective. For the latter, we show that if choosing Pessimistic Value Iteration as the exploitation algorithm to produce π^[[E]], we can achieve a constant regret for risk-averse users independent of the number of episodes K, which is in sharp contrast to the Ω(K) regret for any online RL algorithms in the same setting, while the regret of π^[[O]] (almost) maintains its online regret optimality and does not need to compromise for the success of π^[[E]].